Establishment of a rapid and quantitative method for detecting the range of infection exposure in preclinical dental education - Ayaka Ueda; Yuki Shinoda-Ito; Kazu Takeuchi-Hatanaka; Takashi Ito; Shintaro Ono; Kimito Hirai; Kazuhiro Omori; Tadashi Yamamoto; Shogo Takashiba (BMC Oral Health)
Abstract Backgrounds Safe dental treatments that prevent nosocomial and cross-infections are essential for patients and dental workers. However, dental students sometimes pay inadequate attention to infection control, especially in preclinical practice, because of too much focus on technical training, such as the use of equipment, etc. The spread of infections such as SARS-CoV-2, antibiotic-resistant bacteria, and oral bacteria are sometimes lethal for medically compromised patients. Thus, the rapid and inexpensive detection system to detect and measure dental practice-related infection spread during preclinical treatment is highly desired for dental education. This study aimed to establish a method to quantify and visualize infected areas using dental phantoms for safe and effective preclinical dental practices. Methods At first, we developed artificial saliva as an in vitro study, including food-derived bacteria and fluorescence dye, which is safe for application to preclinical practice education. In vitro study, the correlation between adenosine triphosphate (ATP) levels and Lactobacillus colony numbers in yogurt was examined using the ATP fluorescent method, with colony counting on yogurt only and a mixture of yogurt and ultraviolet (UV)-sensitive hand lotion. The mixed liquid of yogurt and hand lotion was used as artificial saliva. Second, we used this artificial saliva in preclinical education. The degree of contamination of personal protective equipment and dental chairs in preclinical practice using this artificial saliva was determined using the ATP fluorescent method and measuring the luminescence areas among 10 dentists, 10 dental residents, and 10 fifth-grade dental students. Results ATP levels and Lactobacillus colony numbers in yogurt were positively correlated with yogurt alone and a mixture of yogurt and UV-sensitive hand lotions (correlation coefficient ≒ 1). Preclinical education using a mixture of artificial saliva successfully quantified and visualized infectious areas and droplets, which revealed significant differences in ATP amounts in personal protective equipment among groups according to years of experience as dental practitioners (p < 0.05). Conclusions An education system for infection control constructed using artificial saliva containing Lactobacillus and a UV-sensitive fluorescent hand lotion quantified the infectious areas and degrees. Thus, this method is effective in preclinical practice using dental phantoms.